Significance of the Gut-Brain Axis in the Development of Overweight and Obesity - Kuśmierska, Martyna; Kuśmierski, Jakub; Janik, Izabela; Martyka, Anna; Ujma, Przemysław (Journal of Education, Health and Sport, 2024)
Introduction: The global obesity crisis results from inactive lifestyles and poor diets, increasing the risk of metabolic disorders. Emerging research links obesity with gut microbiome changes influenced by factors like age, genetics, and diet. Gut-brain communication via neural, endocrine, and inflammatory pathways, influenced by microbial compounds, affects nervous system function. Materials and Methods of Research: A thorough literature review was performed using PubMed and Google Scholar, employing keywords related to the gut-brain axis and obesity. Results: Obesity shifts gut microbiota composition due to factors like childbirth method, diet, antibiotics, and environment. This imbalance impacts metabolism, appetite, and insulin sensitivity. Gut microbes influence the brain, regulating energy balance and inflammation. Dysregulated tryptophan metabolism leads to insulin resistance. Gut-brain communication via the vagal nerve affects nutrient metabolism. Hormones like insulin and leptin, along with microbial metabolites, affect lipid metabolism and appetite. Gut microbiota abundance correlates with leptin signaling, and changes in ghrelin levels relate to microbiota composition. Microbial presence affects food cravings. Inflammation in obesity is linked to gut microbiota changes, mediated by bile acids and microbial metabolites. Interventions like probiotics and fecal microbiota transplantation offer potential for managing obesity. Emerging therapies like peptide D3 hold promise but require further study. Conclusion: The microbiome-gut-brain axis is vital in obesity, affecting metabolism, inflammation, and appetite. Utilizing interventions such as dietary adjustments and probiotics targeting gut-brain signaling shows promise in managing obesity. Personalized approaches are crucial due to microbiome complexity. Further research is needed to develop effective therapies for the obesity epidemic.